2017
DOI: 10.1155/2017/3054217
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile of Patients with Allergic Rhinitis Caused by Pollen, Mite, and Microbial Allergen Sensitization

Abstract: Allergic rhinitis (AR) is especially prevalent among the population of large cities. Immunologically, the airway epithelium is a region where the population of allergen-presenting cells concentrates. These cells actively express a group of receptors of the innate immune system. A specific cytokine profile is its representation. The study was aimed at evaluating the cytokine profile in patients with seasonal and perennial allergic rhinitis. The cytokine profile of nasal secretion and blood serum of 44 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
(19 reference statements)
1
19
0
2
Order By: Relevance
“…Additionally, one report has shown that IL-33 is activated by GM-CSF and IL-8 in the nasal mucosal epithelium of allergic rhinitis [26]. Moreover, some reports have indicated that production of GM-CSF was activated in patients with seasonal allergic rhinitis (possibly caused by pollen) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one report has shown that IL-33 is activated by GM-CSF and IL-8 in the nasal mucosal epithelium of allergic rhinitis [26]. Moreover, some reports have indicated that production of GM-CSF was activated in patients with seasonal allergic rhinitis (possibly caused by pollen) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of TSLP are increased in the nasal secretion of patients suffering from allergic rhinitis, but there is no evidence directly correlating TSLP expression and pollen allergen-specific IgE levels, suggesting a more general role of TSLP in the initiation and maintenance of a type 2 inflammatory response [ 61 63 ]. In fact, TSLP has been considered a key cytokine driving Th2 polarization through (i) the activation of DCs and macrophages to express OX40 ligand (OX40L), which in turn binds OX40 on naïve CD4 + T cells, and (ii) direct induction of IL4 + and IL-13 + CD4 + T cells [ 64 66 ].…”
Section: Initiation Of Sensitization By Allergenic Pollenmentioning
confidence: 99%
“…Recent studies have shown that type 2 macrophages (M2) can influence IL-4 secretion and the IgE class switch process in cedar pollen-sensitized AR mice [6, 7], which suggests that M2 macrophages might have a role in the initiation and development of AR.…”
Section: Introductionmentioning
confidence: 99%